PENGARUH IKLIM KERJA DAN KOMPETENSI GURU TERHADAP PRODUKTIVITAS MENGAJAR GURU SEKOLAH DASAR DI KECAMATAN CIMANUK KABUPATEN PANDEGLANG - Nur Ida Apriani (JTPPm (Jurnal Teknologi Pendidikan dan Pembelajaran) : Edutech and Intructional Research Journal, 2026)
This research is motivated by the suboptimal teaching productivity of Elementary School teachers in Cimanuk District, Pandeglang Regency, which is suspected to be influenced by the school's work climate and Teacher Competence. This study aims to analyze the influence of work climate and Teacher Competence on teacher teaching productivity, both partially and simultaneously. This study uses a quantitative approach with a survey method. The research population is all Elementary School teachers in Cimanuk District, Pandeglang Regency, with a sampling technique using proportional random sampling. Data collection is carried out through questionnaires that have been tested for validity and reliability. Data analysis techniques use simple linear regression and multiple linear regression with the help of the SPSS program. This study is expected to show that work climate has a positive and significant effect on teacher teaching productivity, Teacher Competence has a positive and significant effect on teacher teaching productivity. Thus, improving a conducive work climate and high Teacher Competence can increase the teaching productivity of Elementary School teachers in Cimanuk District, Pandeglang Regency.